Isolation, purification, and characterization of urease from pigeon pea (cajanus cajan) - Yu, Gracia
Urease (Urea aminodohydrolase, E.C. 3.5.1.5.) was isolated and purified from pigeon pea (Cajanus cajan) b a series of citrate buffer extractions and chromatography through Sephadex Fine G-200. The molecular weight of the enzyme, obtained through Sephadex G-200 chromatography, was estimated at 540,000 daltons. SDS polyyacrylamide gel electrophoresis set the molecular weights of the subunits at 90,000, 46,000, and 31,000 daltons respectively. The isoelectric point, determined by isoelectric focusing, was about 5.8. Thiosemicarbazide was slightly acted upon while urea was fully hydrolyzed by this enzyme. The Km value obtained from the Linbeweaver-Burk plt was 9.9 x 10 -3 M and Vmax value of 189 units/mg protein. The Eadie Hofstee diagnostic plot rendered values of 10.4 x 10 -3 M and 193 units/mg protein for Km and Vmax respectively. The optimum conditions for the assay, with urea as substrate, were at pH 7.0 and temperature at 40 oC. Although Cu 2+ activated the enzyme at high metal concentration (8.16 ppm), a 0.163 ppm inhibits the enzyme activity, thus the order of inhibition at metal concentration of 0.163 ppm was Ni 2+ > Cu 2+ > Ca 2+ > Mg 2+. The crude enzyme was stable when suspended in 50% glycerol and stored at 0 oC for 6 months.